Exploring Customer Experiences and Perceptions towards the Implementation of Digital Banking Services: A Case Study of Millennials in Mandailing Natal - Rukiah (Involvement International Journal of Business, 2024)
This qualitative study investigates the perceptions and experiences of millennials regarding the implementation of digital banking services in Mandailing Natal. Through in-depth interviews with a purposive sample of millennials, key insights have emerged. Convenience and accessibility emerged as paramount factors driving millennials' adoption of digital banking services. Participants highly valued the ability to conduct banking transactions anytime, anywhere, through user-friendly mobile apps. Trust and security were also crucial, with concerns about privacy and security prevalent among participants. Financial institutions must prioritize robust security measures and transparent communication to build trust and encourage adoption. Additionally, the study revealed diverse preferences and usage patterns among millennials, emphasizing the need for tailored digital banking offerings. Education and awareness emerged as essential in shaping millennials' attitudes, highlighting the necessity for improved communication efforts from financial institutions. Understanding and addressing the needs, preferences, and concerns of millennials are crucial for enhancing the adoption and utilization of digital banking services in Mandailing Natal. By prioritizing convenience, trust, personalization, and education, financial institutions can better meet millennials' evolving needs and foster greater engagement and satisfaction with digital banking services.